Revisiting the Role of Cultural Capital in East Asian Educational Systems: The Case of South Korea - Byun, Soo-yong (2012)
The concept of cultural capital has proved invaluable in understanding educational systems in Western countries, and recent work seeks to extend those insights to the diverse educational systems of other geographic regions. We explored cultural capital in South Korea by investigating the relationships among family socioeconomic status (SES), cultural capital, and children's academic achievement using data from the 2000 Programme for International Student Assessment. South Korea was compared with Japan, France, and the United States to understand how institutional features of South Korean education shape the role of cultural capital in academic success. Results showed that family SES had a positive effect on both parental objectified cultural capital and children's embodied cultural capital in South Korea, consistent with evidence from the other countries. Moreover, parental objectified cultural capital had a positive effect on children's academic achievement in South Korea. In contrast to other countries, however, children's embodied cultural capital had a negative effect on academic achievement in South Korea controlling for the other variables. We highlighted several institutional features of South Korean education including a standardized curriculum, extreme focus on test preparation, and extensive shadow education, which may combine to suppress the effect of children's embodied cultural capital on academic achievement.